2014
DOI: 10.1158/1078-0432.ccr-13-2500
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: microRNAs, Cancer Cells, and Microenvironment

Abstract: One of the most unexpected discoveries in molecular oncology over the last decade is the interplay between abnormalities in protein-coding genes and short non-coding microRNAs (miRNAs) that are causally involved in cancer initiation, progression, and dissemination. This phenomenon was initially defined in malignant cells; however, in recent years, more data have accumulated describing the participation of miRNAs produced by microenvironment cells. As hormones, miRNAs are released by a donor cell in various for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 55 publications
1
89
0
1
Order By: Relevance
“…The tumor microenvironment (TME) plays critical roles in the initiation, development, and progression of cancer. The TME includes extracellular matrix as well as different types of cells, including cancer‐associated fibroblasts (CAFs), tumor‐associated macrophages (TAMs), endothelial cells, pericytes, and immune cells (Berindan‐Neagoe and Calin, 2014; Friedl and Alexander, 2011; Laberge et al ., 2012). …”
Section: Transfer Of Biological Information Between Tumor Microenviromentioning
confidence: 99%
“…The tumor microenvironment (TME) plays critical roles in the initiation, development, and progression of cancer. The TME includes extracellular matrix as well as different types of cells, including cancer‐associated fibroblasts (CAFs), tumor‐associated macrophages (TAMs), endothelial cells, pericytes, and immune cells (Berindan‐Neagoe and Calin, 2014; Friedl and Alexander, 2011; Laberge et al ., 2012). …”
Section: Transfer Of Biological Information Between Tumor Microenviromentioning
confidence: 99%
“…Further work from all around the world, reported in over 25,000 publications till date present days, deeply dissected the roles of miRNAs in tumors, both in malignant cells and in the tumor microenvironment cells (13). Also, mutations within microRNAs were identified as more prevalent in malignant cells as compared to normal cells, which shows that these mutations have a role in the malignant phenotype.…”
Section: Micrornas Alterations Are Identified Micrornas Alterations Amentioning
confidence: 98%
“…miR-15a and miR-16-1 reduced expression in prostate cancer promoted tumor growth and progression by the lack of repression of FGF-2 and its receptor FGFR1. Both FGF-2 and its receptor act on tumors cells as well as the surrounding stroma environment to enhance cancer cell survival, proliferation and metastasis and were identified as downregulated also in cancer-associated fibroblasts (CAFs) from the environment of prostate tumors (13). microRNA expression signatures from microRNA expression signatures from tumors or body fluids associates with tumors or body fluids associates with patients' prognosis and overall survival patients' prognosis and overall survival…”
Section: Micrornas Alterations Are Identified Micrornas Alterations Amentioning
confidence: 99%
See 1 more Smart Citation
“…239 It has been suggested that certain miRNAs are key players in cancer processes, possibly in the tumour microenvironment where these short transcripts regulate protein expression via translation inhibition or mRNA degradation. 239,240 The current theories of the mechanism of PNI revolve around interplay between the tumour and nerve within the tumour microenvironment. LOXL2 and FOXC2 both drew attention due to their apparent role in EMT, which could trigger the cellular migration, invasion and spread seen in clinical PNI.…”
Section: Discussionmentioning
confidence: 99%